(untitled) - Abraham, Paul (Upper Saddle River, New Jersey, 1997)
This book presents readings that offer cross-cultural perspectives and generate class discussion on students' impressions of the U.S. on topics such as cities, food, culture shock, retirement, equality for all, racial issues, taxes, and freedom of religion.
Keywords: english language,english language,english language,readers; glossaries, vocabularies, etc,study and teaching,textbooks for foreign speakers